Molecular analysis of edible bird's nest and rapid authentication of Aerodramus fuciphagus from its subspecies by PCR-RFLP based on the cytb gene. Issue 21 (18th May 2020) - Liu, Kunfeng; Wu, Maoyong; Lin, Xuemei; Lonan, Piyanuch; Chen, Sitai; Wu, Yina; Lai, Xiaoping; Yu, Liangwen; Zhou, Xiaoming; Li, Geng
Abstract : The PCR-RFLP method can efficiently distinguish A. fuciphagus from its subspecies and other species based on the cytb region. Abstract : Edible bird's nest (EBN), for its great nutritional value, is widely used around the world, especially in China and Singapore. EBNs of different origins and types may vary in price and quality. Nowadays, birds' nests are difficult to identify morphologically, except for some whole bird's nests of which origins can be roughly identified. In this study, forty-two samples were collected from different regions for sequencing analysis and phylogenetic classification to initially determine their origins. Two stable enzyme digestion sites were found in the analysis of restriction maps of the species. Then, a quick and specific PCR-RFLP method was established to identify the EBN samples' origins. The genetic identification results indicated that the forty-two samples were from five origins. With the Af/g-486bp-F/R primer and restriction enzyme Taq I, Aerodramus fuciphagus ( A. fuciphagus ) was efficiently differentiated from the other species. Furthermore, the cytb-592bp-F/R primer and the BamH I enzyme were found to be useful in distinguishing Aerodramus fuciphagus ( A. fuciphagus ) from its subspecies ( Aerodramus germani, A. germani ). The PCR-RFLP method provides a potential tool for the rapid discrimination of A. fuciphagus at the species and even the subspecies levels to ensure the quality of the EBN products.